Pengembangan Media Pembelajaran Books Vokal Kids Untuk Meningkatkan Kemampuan Pengenalan Huruf Vokal Pada Anak Usia 5-6 Tahun - Sholihah, Nur Afidatus; Komalasari, Dewi; Reza, Muhammad; Adhe, Kartika Rinakit (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Early childhood literacy fundamental is heavily reliant on the ability to recognize vowel letters. This study aims to determine the feasibility, practicality, and effectiveness of the